Using Word Square Game to Improve Students’ Vocabulary Achievement - Suri, Atika; Husnayaini, Ihda; Indrawati, Indrawati (EEdJ: English Education Journal, 2023)
The purpose of this study was to determine the impact of using the Word Square approach on students' vocabulary achievement. Students in the eighth grade from a public junior high school in Mendo Barat, Bangka Belitung, were chosen as the sample for an experimental type of research and separated into two groups using a quasi-experimental design: the experimental group and the control group. The test was the instrument employed in this study, and the t-test analysis was performed to assess the test data. The test result was analyzed statistically using the Paired Sample T-Test and the Independent Sample T-Test. It revealed that the experimental and control groups' respective mean pre- and post-test differences were 34.268 and 33.334. Additionally, the t-obtained post-test value of 1.549 was greater than the essential t-table value of 2.01. The findings suggested that the null hypothesis was disproved and the alternate hypothesis was found. According to the findings, the Word Square was one of the most successful strategies for increasing students' passion for studying English.